2018
DOI: 10.1093/jpids/pix093
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Coronavirus Infection in Children: The Role of Viral Factors and an Immunocompromised State

Abstract: The presence of a copathogen and host factors, including an immunocompromised state, were associated with increased risk for severe LRTD. Recognizing risk factors for severe respiratory illness might assist in risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
152
4
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 38 publications
7
152
4
6
Order By: Relevance
“…Clinical studies have shown that coronavirus infection severity was linked to patient health status and an immunocompromised state carried an increased risk of death 6,7 . Clinical studies have shown that coronavirus infection severity was linked to patient health status and an immunocompromised state carried an increased risk of death 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that coronavirus infection severity was linked to patient health status and an immunocompromised state carried an increased risk of death 6,7 . Clinical studies have shown that coronavirus infection severity was linked to patient health status and an immunocompromised state carried an increased risk of death 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent individuals they usually infect the upper respiratory tract, where they are mainly associated with 15-30% of upper respiratory tract infections (URI): rhinitis, laryngitis/pharyngitis as well as otitis. Being highly opportunistic pathogens [14], HCoV can reach the lower respiratory tract and be associated with more severe illnesses, such as bronchitis, bronchiolitis, pneumonia, exacerbations of asthma and respiratory distress syndrome [17,31,[208][209][210][211][212][213][214].…”
Section: Human Coronaviruses: Eclosions Of Recognized Respiratory Patmentioning
confidence: 99%
“…2,[8][9][10] This is consistent with data for other coronaviruses, which do cause more severe infections in immunocompromised children. 11 To evaluate this, we used a flash survey to determine whether there was current evidence that pediatric patients with cancer in SARS-CoV-2 affected areas had been tested for this virus or had developed severe COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%